Jose Luis Brea. Theory-criticism in the age of the world-Internet. (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
Focusing on a specific period of J. L. Brea's theoretical practice, we carry out a critical analysis of two fundamental concepts in his work: RAM culture and electronic cultural capitalism. From this, a series of discursive tensions are derived regarding the fetishism of merchandise in the world-Internet era and its implications in the regime of construction of contemporary subjectivities, towards a differential conceptualization in contemporary thought.
Keywords: Digital Culture; Fetish; Capitalism